(untitled) (Global Journal of Medical Research, 2022)
Mellitus Diabetes (DM) is a metabolic disorder manifested by an increase in blood glucose level. Lack of insulin secretion by pancreatic β-cells or insulin resistance are factors that contribute to the development of DM. Insulin resistance is affected by a number of factors including oxidative stress, leading to the formation of type 2 diabetes Mellitus (T2DM) or insulindependent diabetes which is a major and rapidly growing global problem through several cellular processes. The current review is a brief account of the various aspects of oxidative stress and their association with diabetes in various ways in which oxidative stress contributes to the pathophysiology of insulin resistance to diabetes.